When Mind Hurts the Skin: A Rare Case of Dermatitis Artefacta in an Epileptic Female - Maaz ullah; Tayyeb Ali; Muhammad Hassaan Javaid; Muddassir Khalid; Naveed Ahmad; Farooq Haider; Okasha Tahir; Munazza Iqbal; Sadia Afridi; Ejaz Ali; Fred Segawa (Clinical Case Reports, 2026)
ABSTRACT DA is an uncommon psychocutaneous disorder in which the patient intentionally induces lesions to satisfy a subconscious psychological need and, at the same time, denies self‐harm. DA typically presents as bizarre, well‐demarcated lesions in accessible areas. Diagnosis is based on the suspicion and exclusion of organic causes. A 27‐year‐old married woman presented with painful, slow‐healing ulcers on the dorsum of both hands and forearms for 2 months, along with body pain and progressive hair loss. The patient had epilepsy, which was controlled with sodium valproate and carbamazepine, although she had occasional psychogenic non‐epileptic seizures (PNES). She denied systemic symptoms, like fever or arthralgia. Examination revealed irregular punched‐out ulcers with erythematous borders, crusting, and post‐inflammatory hyperpigmentation and infection or signs of systemic illness. Investigations revealed leukocytosis (TLC 19.1 × 10 9 /L), while the brain CT was normal. Skin biopsy revealed epidermal ulceration, necrosis, and mixed inflammatory infiltrates without vasculitis or pathogenic organisms. The patient was admitted to the hospital to manage her lesions when experiencing anxiety attacks, thereby confirming DA. This case represents the typical features of DA: self‐inflicted geometric lesions on accessible sites in a young woman with psychological stressors. The coexistence of epilepsy and pseudoseizures reflects a psychoneurological interaction whereby chronic illness and emotional instability may be the instigators of maladaptive behavior. Management requires a multidisciplinary approach involving dermatology, psychiatry, and neurology. Supportive topical therapy and cognitive‐behavioral therapy resulted in better emotional regulation, adequate sleep, and ulcer healing. Empathetic, integrated management ensures recovery and prevents the recurrence of DA.